2016
DOI: 10.3844/ajavsp.2016.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Pathologies of Acute Interstitial Pneumonia in Feedlot Cattle

Abstract: Acute Interstitial Pneumonia (AIP) is a costly issue that affects feedlot cattle. Research has yet to elucidate the etiology of AIP; therefore a case-control study was conducted to evaluate possible management and physiological factors that contribute to AIP in feedlot cattle. The experiment was conducted during the summer of 2011 in a commercial feedyard in Kansas. Animals exhibiting clinical signs of AIP and a control animal from the same pen were selected for ante-mortem examination. Post-mortem AIP cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…In a case-control study, different management and physiological factors that may contribute to AIP in feedlot cattle were studied [ 18 ]. Affected animals and normal pen-mates were subjected to antemortem and postmortem examinations [ 18 ]. In this study, the rectal temperature and rumen pH values in AIP cattle were higher than normal pen-mates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a case-control study, different management and physiological factors that may contribute to AIP in feedlot cattle were studied [ 18 ]. Affected animals and normal pen-mates were subjected to antemortem and postmortem examinations [ 18 ]. In this study, the rectal temperature and rumen pH values in AIP cattle were higher than normal pen-mates.…”
Section: Resultsmentioning
confidence: 99%
“…Bronchiolitis and bronchopneumonia were evident in most of the affected animals. The authors reported no association between AIP and feed intake patterns, serum amylase, or lipase levels [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations